Reduction in Sample Recollection Number Following the Implementation of Automated Pre-Analytical Interference Detection in Coagulation Testing - Vitória Luiza Camargo Milczarski; Iuri Vicente Camargo Morkis; Camila da Silveira Mariot; Gabriel Giron Correa; Carine Ghem (Annals of Clinical Biochemistry: International Journal of Laboratory Medicine, 2026)
Background: Pre-analytical interferents such as hemolysis, lipemia, and icterus are major sources of error in coagulation testing and frequently lead to sample recollection. Visual inspection, although widely used, is subjective and may fail to identify unsuitable samples. Automated pre-analytical interferent detection using hemolysis, icterus, and lipemia (HIL) indices has been introduced to improve reliability and laboratory efficiency. Objective: Evaluate the impact of automated pre-analytical interferent detection on the number of sample recollections due to hemolysis in routine coagulation tests. Methods: A retrospective study compared two one-year periods in a tertiary hospital laboratory. In 2022, samples were assessed by visual inspection using the STA-R® analyzer, while in 2023 automated inspection was implemented using the ACL Top® 750 system. Recollections due exclusively to hemolysis were analyzed for PT, aPTT, FV, fibrinogen, and D-dimer tests. Statistical analyses included binomial, Wald, and Student’s t tests, with p ≤ 0.005 considered significant. Results: A significant reduction in recollections was observed after implementation of automated inspection (0.49% vs. 0.35%; p < 0.001). PT showed a statistically significant decrease in recollections (p = 0.003), while other tests demonstrated non-significant reductions. Monthly average recollections decreased by 18.9% (p < 0.001). Annual costs related to recollections were reduced from US$ 638.49 to US$ 399.74, representing savings of US$ 238.75. A significant reduction was also observed in emergency department recollections. Conclusions: Automated pre-analytical interferent detection significantly reduced hemolysis-related recollections, costs, and subjectivity in coagulation testing, supporting its implementation as a valuable tool to improve laboratory workflow and result reliability.